Evaluation of Cash Disbursement Accounting Systems and Procedures at the Government Agency of the Sidenreng Rappang District Health Office - Maghfirah, Annesa Tasya; Haliah , Haliah; Nirwana, Nirwana (Westscience Press, 2025)
This study seeks to evaluate the extent to which the cash expenditure accounting system and procedures of the Sidenreng Rappang Regency Health Office comply with Minister of Home Affairs Regulation Number 77 of 2020. The variable under investigation is the complete cash expenditure procedure and methodology. This study seeks to ascertain the compliance of the cash spending system and procedures of the Sidenreng Rappang Regency Health Office with the regulations specified in the Regulation of the Minister of Home Affairs (Permendagri) Number 77 of 2020. Documentation, interviews, and observation were the methods utilized to get the data. In this study, qualitative descriptive data analysis was employed. The study's findings demonstrate that the Sidenreng Rappang Regency Health Office's accounting system and inventory spending practices are in compliance with the Minister of Home Affairs' (Permendagri) Regulation Number 77 of 2020 regarding Technical Guidelines for Regional Financial Management. Related documents such as the Letter of Provision of Funds (SPD), Payment Request Letter (SPP), Payment Order (SPM), Fund distribution Order (SP2D), and Letter of Accountability (SPJ) have assisted the implementation of cash distribution.